Duck gasdermin E is a substrate of caspase-3/-7 and an executioner of pyroptosis - Li, Hanqing; Wang, Xin; Yu, Lanjie; Wang, Junwei; Cao, Yongsheng; Ma, Bo; Zhang, Wenlong (Frontiers in Immunology, 2023)
Gasdermin (GSDM)-mediated cell death is an ancient immune defensive mechanism that plays an essential role in bacteria, fungi, coral, teleost, and mammals. After being cleaved by proteases of hosts or pathogens, amino-terminal (NT) fragment of GSDMs (GSDM-NTs) form pores in the cell membrane, thereby leading to pyroptotic cell death. However, the expression profile, activation mechanism and function of avian GSDMs have not been clearly demonstrated. In the current study, genes encoding duck gasdermin E (duGSDME), caspase-3 (ducaspase-3) and ducaspase-7 were cloned from a virus-challenged duck embryo. The cleavage of duGSDME by ducaspase-3/-7 was verified in both a cell-free system and in HEK293 cells. Ducaspase-3/-7 recognized and cleaved duGSDME at 270DAVD273. Overexpression of duGSDME-NT (1-273aa) fragment led to pyroptosis-like morphological change, increased lactic dehydrogenase (LDH) release and propidium iodide uptake of HEK293 cells and increased LDH release of MDCK cells, which indicated the cell membrane damaging ability of duGSDME-NT. In addition, recombinantly expressed duGSDME-NT showed weak bactericidal activity to an enterotoxic Escherichia coli (F5+) strain. Using the prepared anti-duGSDME-NT and anti-ducaspase-3 antibodies, the current study determined that the expression level of duGSDME in tissues of the duckling is low and DHAV-3 challenge can upregulate duGSDME and ducaspase-3 expression and activation in different tissues. The results indicated that duGSDME is a substrate of ducapsase-3/-7 and duGSDME-NT has the ability to cause pyroptosis. In addition, ducaspase-3/-7-mediated duGSDME cleavage may play a role in the immune defense of ducks against infectious diseases. The current study provides essential information for further investigation of avian innate immunity and avian diseases.